Isolation and screening of phosphorus solubilizing bacteria from saline alkali soil and their potential for Pb pollution remediation - Zhang, Chaonan; Chen, Haoming; Dai, Yao; Chen, Yan; Tian, Yuxin; Huo, Zongli (Frontiers in Bioengineering and Biotechnology, 2023)
The high pH and salinity of saline alkali soil not only seriously restrict the growth of crops, but also aggravate the pollution of heavy metals. The fixation of heavy metals and the regulation of pH by phosphorus solubilizing microorganisms may become a new way to repair heavy mental and improve saline alkali soil. In this study, a saline-alkali resistant bacteria (CZ-B1, CGMCC No: 1.19458) was screened from saline-alkali soil, and its tolerance to salt/alkali/lead stress was investigated by shaking flask experiment. The strain was identified as Bacillus amyloliquefaciens by morphology and 16S rRNA gene sequence analysis. The optimum growth temperature of CZ-B1 is about 35°C–40℃. The maximum salt stress and pH that it can tolerance are 100 g/L and 9 respectively, and its tolerance to Pb2+ can reach 2000 mg/L. The phosphorus release amount of CZ-B1 to Ca3(PO4)2 within 72 h is 91.00–102.73 mg/L. The phosphate solubilizing index in PVK agar medium and NBRIP agar medium are more than 2, which can be defined as phosphate solubilizing bacteria. Moreover, the dissolution of CZ-B1 to phosphorus is mainly attributed to tartaric acid, citric acid and succinic acid in inorganic medium. In addition, the removal rate of Pb2+ by CZ-B1 can reach 90.38% for 500 mg/L. This study found that CZ-B1 can immobilize Pb through three biological mechanisms (organic acid, extracellular polymers and mineralization reaction). The release of succinic acid (10.97 g/L) and citric acid (5.26 g/L) may be the main mechanism to promote the mineralization reaction of CZ-B1 (phosphate and oxalate) and resistance to Pb stress. In addition, the high enrichment of Pb2+ by EPS can increase the rate of extracellular electron transfer and accelerate the mineralization of CZ-B1. The screening and domestication of saline-tolerant phosphorus-solubilizing bacteria not only help to remediate Pb contamination in saline soils, but also can provide P element for plant growth in saline soil.